Regeneration of Salicaceae riparian forests in the Northern Hemisphere: A new framework and management tool. (15th July 2018) - González, Eduardo; Martínez-Fernández, Vanesa; Shafroth, Patrick B.; Sher, Anna A.; Henry, Annie L.; Garófano-Gómez, Virginia; Corenblit, Dov
Abstract: Human activities on floodplains have severely disrupted the regeneration of foundation riparian shrub and tree species of the Salicaceae family ( Populus and Salix spp.) throughout the Northern Hemisphere. Restoration ecologists initially tackled this problem from a terrestrial perspective that emphasized planting. More recently, floodplain restoration activities have embraced an aquatic perspective, inspired by the expanding practice of managing river flows to improve river health (environmental flows). However, riparian Salicaceae species occupy floodplain and riparian areas, which lie at the interface of both terrestrial and aquatic ecosystems along watercourses. Thus, their regeneration depends on a complex interaction of hydrologic and geomorphic processes that have shaped key life-cycle requirements for seedling establishment. Ultimately, restoration needs to integrate these concepts to succeed. However, while regeneration of Salicaceae is now reasonably well-understood, the literature reporting restoration actions on Salicaceae regeneration is sparse, and a specific theoretical framework is still missing. Here, we have reviewed 105 peer-reviewed published experiences in restoration of Salicaceae forests, including 91 projects in 10 world regions, to construct a decision tree to inform restoration planning through explicit links between the well-studied biophysical requirements of Salicaceae regeneration and 17 specific restoration actions, the most popular being planting (in 55% of the projects), land contouring (30%), removal of competing vegetation (30%), site selection (26%), and irrigation (24%). We also identified research gaps related to Salicaceae forest restoration and discuss alternative, innovative and feasible approaches that incorporate the human component. Highlights: We reviewed 105 articles reporting 91 Salicaceae restoration projects worldwide. We developed a decision tree for restoring the regeneration of Salicaceae forests. Restoration actions are linked to biophysical requirements for plant establishment. Planting, land contouring, and vegetation removal are the most frequently applied. Environmental flows are an effective alternative for the less populated areas.